(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
In this paper, the design and fabrication of modified Sierpinski carpet fractal antenna is studied. The analysis took place between ranges of 0.5 GHz to 6 GHz. A Planar antenna with Microstrip feed modified Sierpinski carpet fractal geometry for multiband applications are presented. The multiband behavior is analyzed through two fractal iterations. Self similarity property of fractal technology is applied in the antenna design to reduce the physical size, increase bandwidth and gain. The parameters of the antenna such as radiation pattern return loss directivity, gain, radiation efficiency are simulated using the IE3D electromagnetic simulator